Family Caregiver Phenomenon that Treats Persons with Disabilities Since Birth - Halawiah Wia Musi (Faculty of Medicine, Public Health, and Nursing, 2020)
Background: Disability is a disturbance or limitation of physical activity involving participation restrictions. The disturbance is a problem in the body’s function and its structure. Restrictions on physical activity are the difficulties faced in performing tasks or actions, while limiting participation is a problem experienced by individuals in engagement in life situations. Objective: This study aimed to provide an in-depth description of the feelings, explain the obstacles or difficulties experienced and explain the caregiver’s expectations of mothers/fathers/brothers in caring for children with disabilities from birth. Method: This study was a qualitative research with a descriptive phenomenology approach. Data collection was conducted through in-depth interviews of family caregivers of persons with disabilities since birth with inclusion and exclusion criteria. The data were analyzed by Colaizzi’s method and data triangulation was performed by a coder to maintain data validation. The sample selection was done by purposive sampling. The sample of the study amounted to 17 persons who were family caregivers. Result: The results showed that caregiver phenomenon in caring for persons with disabilities since birth is a burden. Psychological burdens include sadness, disappointment, anger, guilt, depression and ultimately acceptance. Additionally, there are financial burdens, time constraints and social stigma. Conclusions: Caregivers for persons with disabilities since birth experience several burdens, including psychological, physical, financial and social burdens. There is the psychological burden of anger, disappointment, fear, worry, and guilt which many finally can accept. The physical burden of fatigue, lack of sleep, lack of appetite may result in diseases such as gastritis, hypertension, along with muscle and joint disorders. Financial burdens are related to medical expenses, transportation, and daily necessities. The social burden involves stigma, negative labeling and lack of time with other families and communities. It is hoped all caregivers with family and community support can accept and overcome these challenges.